Keragaman spesies gastropoda di zona intertidal Pulau Ambon - Sara Haumahu; Prulley A Uneputty (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Intertidal zone has a high diversity of marine organisms including marine gastropods. Many species of marine gastropods were consumed by local communities in Maluku province. Lack of study on marine gastropod species diversities in Ambon Island and unpublished yet. The research on marine gastropods in Ambon Island was conducted with the objectives are to determine species composition, to analyze an ecological density, similarity index, Shannon-Wiener diversity indices (H`), Pileou’s evenness indices (J`) and Simpson dominance indices (D). Sampling was conducted in intertidal zone around Ambon Island at five sampling stations during spring low tide at daytime on December to February 2022. Sampling was done by applying transect line methods. A total of 78 species of marine gastropods found in this research. Species composition and ecological density varies between sampling stations. Similarity index varied from 3,62% to 34,12%. Shannon-Wiener diversity index (H`) varied between H` = 2,10 and H` = 2,84. Pielou’s evenness index (J`) ranged from J`= 0,65 to J` = 0,78. Simpson dominance index (D) varied from D = 0,11 to D = 0,22. There were 9 to17 rare species of marine gastropods which contributed to species diversity, while there were 5-10 common species which contributed to species dominance of marine gastropod communities around intertidal zone of Ambon Island.